2024
DOI: 10.3947/ic.2024.0024
|View full text |Cite
|
Sign up to set email alerts
|

Updated Clinical Practice Guidelines for the Diagnosis and Management of Long COVID

Jun-Won Seo,
Seong Eun Kim,
Yoonjung Kim
et al.

Abstract: "Long COVID" is a term used to describe a condition when the symptoms and signs associated with coronavirus disease 2019 (COVID-19) persist for more than three months among patients infected with COVID-19; this condition has been reported globally and poses a serious public health issue. Long COVID can manifest in various forms, highlighting the need for appropriate evaluation and management by experts from various fields. However, due to the lack of clear clinical definitions, knowledge of pathophysiology, di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 145 publications
0
2
0
Order By: Relevance
“… 36 For example, respiratory rehabilitation therapy is recommended for patients with previous neurological and muscular comorbidity. 37 Finally, the enhancement of self-management specific to the current diseases or symptoms through primary care follow-up empowers patients to actively participate in their own healthcare and achieve improved outcomes. 38 39 …”
Section: Discussionmentioning
confidence: 99%
“… 36 For example, respiratory rehabilitation therapy is recommended for patients with previous neurological and muscular comorbidity. 37 Finally, the enhancement of self-management specific to the current diseases or symptoms through primary care follow-up empowers patients to actively participate in their own healthcare and achieve improved outcomes. 38 39 …”
Section: Discussionmentioning
confidence: 99%
“…Patients eligible for inclusion in this study were individuals aged 18 years or older who had a laboratory-confirmed SARS-CoV-2 infection, verified either by RT-PCR or rapid antigen tests. Additionally, these individuals must have been diagnosed with Post-COVID Syndrome, characterized by a constellation of symptoms persisting for more than 12 weeks after the acute infection, according to guidelines [19]. These symptoms include, but are not limited to, chronic fatigue, shortness of breath, cognitive disturbances ("brain fog"), joint pain, and ongoing loss of taste or smell, without any alternative diagnosis that could explain these symptoms [20].…”
Section: Patients' Inclusion and Exclusion Criteriamentioning
confidence: 99%